ANALISIS MATRIKS BCG (BOSTON CONSULTING GROUP) DALAM STRATEGI MEMPERTAHANKAN PANGSA PASAR PADA SMARTPHONE MEREK SAMSUNG (STUDI KASUS PADA PT. SAMSUNG ELEKTRONIK INDONESIA TAHUN 2019) - Kiki Maristia (Universitas Borneo Tarakan, 2020)
The purpose of this research itself is to determine the market position PT Samsung Elektronik Indonesia in the BCG matrix (Boston Consulting Group) and formulating strategies to maintain market share. This type of research used in this research is to use descriptive methods. While this research data collection technique uses secondary data based on written documents in the form of sales results and market share PT Samsung Elektronik Indonesia. The calculation result of BCG Matrix owned by PT Samsung Elektronik Indonesia shows that the company is in the position of Cash Cows where the position has a medium market growth with high market share. Thus the company can formulate strategies in the form of product development and diversification. Keywords: BCG (Boston Consulting Group Matrix), Implementation of Strategies, Market Share Defense